THE TEACHERS' CLINIC. - Garner, S. Paul (The Accounting Review, 1947)
Abstract The method used for calculating price and quantity variances in standard cost procedure deserves more explanation than is given it in cost accounting textbooks and current accounting literature, as of July 1947. The student in a standard-cost accounting course is likely to be perplexed by the glibness of the instructor in arriving at the amount of variation attributable to price on one hand and quantity on the other. The formula used in commercial practice demands a reasonable explanation since it is mathematically questionable. The purpose of this article is to justify the current practice, and to point out the theoretical issues that are involved. Some accountants, aware of the mathematical biases in calculating price and quantity variations, compute only the total amount of variation, and do not attempt to calculate the amounts of the individual variations attributable to price and quantity. But if the amounts of the individual variations are sufficiently significant to require administrative attention, this expedient will not, of course, prove satisfactory.